“Prezewody” program for capacitance and inductance determination of can-bus transmission lines - Kalita, W.; Kamuda, K.; Sabat, W.; Wisz, B. (Видавництво Національного університету "Львівська політехніка", 2004)
The describing of the computer program which allows to determine residual parameters of the cable system with cylindrical section has been included in the paper. The wire capacitance and inductance, whice are used in data transmission systems (i.e. CAN-bus). have a big influence on parameters of the transmission line. The knowing of these parameters allows to select the optimal conditions of the such systems from the point view of transmission quality and electromagnetic compatibility.